Advancing Cancer Treatment and Diagnosis: A Review on Photodynamic Therapy Using OLED Technology - Rajesh Kumar Tiwari; Rajesh Mishra; Sanjay Kumar Sharma; Nakshathra Prabhu; Mangey Ram Nagar; Saulius Grigalevicius (Molecules)
Photodynamic therapy (PDT) is an innovative and non-invasive approach to treating apparent tumours with minimal toxicity. PDT has a long-standing application in antitumor treatment utilizing various photosensitizers (PSs) for different tumours. Historically, light has served as a therapeutic tool in many diseases. PDT involves a dual treatment process in which light energy and PSs are combined to ablate tumour cells following light activation. In general, PDT exhibits reduced side effects and toxicity compared to chemotherapy and radiotherapy, as it spares the extracellular matrix, facilitating excellent tissue healing and minimizing scarring. In addition, PSs can serve in diagnostic roles in tumour identification, termed photodynamic diagnosis (PDD). Advancements in flexible light sources that produce uniform illumination could significantly enhance the consistency of light delivery. This review outlines the clinical applications of OLEDs in PDT for cancer, addressing both diagnostic and therapeutic methods. Furthermore, we will explore various tumour cases using PDT with OLEDs. In particular, antimicrobial PDT targets antibiotic-resistant strains in diabetic foot ulcers, while metronomic PDT promotes cancer cell apoptosis through prolonged, low-intensity light exposure. Our emphasis is on PDT employing organic light-emitting diodes (OLEDs). Furthermore, the combination of PDT with NIR-OLEDs is examined for its potential to enhance tumour-targeting effectiveness, possibly exceeding the results of standalone treatments.